Introducing loop-closure for phosphates into a provincial development strategy: An analysis of overlaps of primary and secondary phosphate processing technologies - Vidima, Sizwe (Department of Chemical Engineering, 2019)
Almost 90% of the global phosphoric acid demand can primarily be linked to fertiliser production for application onto agricultural lands (PotashCorp, 2014). To fulfil the phosphate fertiliser demand in South Africa’s arable soils, the country largely relies on the mining and processing of the extensive igneous phosphate ore deposits found in Phalaborwa, Limpopo (DMR, 2008); but this extractive approach to procuring phosphates is not sustainable. Moreover, due to rising phosphate demands and declining ore grades, worldwide phosphate ore reserves are expected to last only approximately 100 - 400 years (Smil, 2000). The intensification of phosphate resource consumption has also resulted in increased phosphate loads in wastewater treatment plant (WWTP) influents thereby exerting pressure on existing treatment systems and potentially, on water ecosystems in which these phosphates end up. Therefore, it is because of the myriad difficulties associated with linear phosphate resource flows that there has been ongoing research on the recovery of phosphate nutrients from wastewater (Durrant, et al., 1999; Levlin and Hultman, 2004; Sikosana, 2015) and sourceseparated urine (Ganrot, 2005; Pronk and Kone, 2009). Consequently, the purpose of this dissertation is to investigate a novel approach to loop-closure through the recovery of urine-bound phosphates. Uniquely, this research considers the subsequent integration of the recovered phosphate into existing primary phosphate processing facilities – stimulated by a process to develop a sub-national minerals beneficiation strategy for the kwaZulu-Natal (KZN) province in South Africa. Not only does the investigation seek to understand the technical potential of reintroducing waste-bound phosphates into the phosphate value chain but it also seeks to understand the potential for the respective contribution into the socio-economic sphere of sustainable development through employment creation. Three research approaches were used in obtaining results in this dissertation. Firstly, flowsheet simulations of Dihydrate phosphogypsum (DH) and Hemihydrate phosphogypsum (HH) producing processes were done. The materials balance simulations included a base case where a secondary phosphate source was not introduced in the process and the case where it was introduced into the processes in the form of struvite recovered from sanitation infrastructure. Secondly, a socio-economic assessment was carried out. This involved a cost analysis of implementing a reverse logistics network that collects urine from non-sewer-served areas, processes it into struvite and transports the struvite into a phosphoric acid complex, such as the one owned by Foskor in Richards Bay. In addition to this, the quantity of jobs was determined. Lastly, interviews and desktop research were used to learn about past experiences in recycling thereby providing insight regarding key considerations when implementing extended producer responsibility schemes. With the assumptions that are detailed in Chapter 3, the results of Chapter 4 reveal that it should be possible, from a technical standpoint, to integrate struvite into existing phosphoric acid generation processes. However, the use of struvite in such a process raises concern in the form of loss of phosphoric acid production if the feed tonnage is kept constant. Furthermore, there is a presence of magnesium in the product acid which has been known to adversely affect the formation of gypsum crystals. Additionally, when using the struvite cost obtained from Sikosana (2015) it can be argued that there is little to no process-related financial benefit in integrating struvite in a phosphoric acid generation complex such as the investigated DH and / or HH processes. The socio-economic analysis showed that implementing a reverse logistics network for the recycling of phosphates would cost 147,000 ZAR per ton of struvite generated whilst creating approximately 9,000 to 18,000 jobs (depending on the approach) in the respective collection, processing and transportation phases in recycling, if urine collection were to be extended to all households in KZN not served by network sewer systems. Furthermore, the study revealed that the funding model in the extended producer responsibility scheme would have to contribute an average of 152,000 ZAR per year, through some form of subsidy, for every job that exists in the network. Critical insight was drawn from the literature study and interviewing process. It was found that the key considerations that need attention when setting up an extended producer responsibility (EPR) scheme include a well-governed and aligned producer responsibility organisation (PRO) to assist the producer in achieving their respective production targets. Secondly, there is evidence that mandatory approaches to EPR funding have been less successful as funding approaches for EPR schemes in South Africa; in fact, the more successful EPR schemes have been voluntary / industry driven approaches. As a basis, the work in this dissertation can be used in influencing future work in the phosphate loop-closure context. It can then be concluded that the return of urine-derived struvite, as a secondary phosphate raw material, into industrial phosphoric acid processing should be technically possible. In doing so, a more circular phosphate value chain could be achieved. The reintroduction of a secondary phosphate source in the HH and DH processes would therefore bring about new work opportunities, and thus the upliftment of the socio-economic status of the individuals involved in the reverse logistics that facilitate struvite supply. It is recommended that technical questions, for example the specifics of how struvite interacts with sulphuric acid, be further investigated from a thermodynamic and reaction kinetics perspective. Also, there is enough evidence to start an expert discussion about the suitability of existing mechanisms that have been accepted and used by industrial producers to give effect to their extended environmental responsibilities, for application in phosphate loop-closure.